PR TIKET.COM COMMUNICATION CRISIS IN RESPONDING TO COMMENTS BY USERS ON INSTAGRAM @TIKETCOM DURING THE COVID-19 PANDEMIC - Kevin Anggering Hanevie; Kusnarto (JOSAR (Journal of Students Academic Research), 2023)
This study was designed to understand how Tiker.com responded to the crisis of comments posted on Instagram @tiketcom by tiket.com users during the COVID-19 pandemic. If social media is your vehicle for discovering the problems users are facing, you can follow up by interacting in the comments section of @tiketcom Instagram posts regarding the crisis. This survey data is in the form of text, images, and videos from @tiketcom Instagram posts from 18 September 2020 to 2 July 2021. This research is a qualitative research. The methodology used in this study is Situational Crisis Communication (SCCT) to understand the crisis model used by PR Tiket.com. SCCT theory suggests that a crisis in an organization is a threat because it affects the reputation created by the crisis, so that the right strategy is needed to deal with the crisis. The research was conducted in three stages: data exploration, data analysis, and discussion of the resulting data. PR Tiket.com uses a messaging strategy in every post to provide information on the latest developments during the COVID-19 pandemic, the messaging strategy consists of eight messaging categories, namely; accommodative strategies, anti-social or defensive, emphasising inter-organisational relationship, excellence or renewal, framing the crisis, framing the organization, routine communication, self-enhancement. The results of this study indicate that Tiket.com PR uses SCCT theory in every crisis given by user comments on @tiketcom Instagram posts when facing a comment crisis during the COVID-19 pandemic.